Double Higgs production at the LHC as a robust test of little Higgs model - Dib, C. O.; Rosenfeld, R.; Zerwekh, A.; Simak, V; Leitner, R.; Valkarova, A.; Valenta, J. (Amer Inst Physics, 2006)
We analyze double Higgs boson production at the LHC in the context of Little Higgs models. In double Higgs production, the diagrams involved are directly related to those that cause the cancellation of the quadratic divergence of the Higgs self-energy, so this mode provides a robust prediction for this class of models. We find that in extensions of this model with the inclusion of a so-called T-parity, there is a significant enhancement in the cross sections as compared to the Standard Model.
Keywords: Higgs boson; little Higgs model